TENDENCIES OF TRANSFORMATION IN THE PARADIGMS OF LIFE GOALS IN THE INFORMATION AGE - Sanjar Sindorqulovich Karimov (Journals Park Publishing, 2025)
This article analyzes the tendencies of transformation in the paradigms of life goals in the information age. While life goals in traditional society were based on national values and social traditions, it is emphasized that in the modern global context, personal freedom, individual interests, and technological opportunities are becoming of primary importance.
Keywords: Life goals, paradigm, informatization, globalization, personal freedom, individual interests, national values, universal principles, motivation, reflection, innovation